Meta-Analysis: Effect Size of Problem-Based Learning Models on Students' Higher Order Thinking Skills (HOTS) and Conceptual Understanding in Physics - Erlangga, Sony Yunior; Poort, Elang Amadeus; winingsih, Puji Hariati; Manasikana, Oktaffiarinna; Dimas , Arifian (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effect size of implementing problem-based learning (PBL) models on students' Higher Order Thinking Skills (HOTS) and conceptual understanding. Although these higher-order skills are crucial in learning and everyday life, students' understanding in this area remains low. This research employs a meta-analysis method by analyzing 20 articles from various accredited Sinta journals related to the effects of PBL models on students' HOTS and conceptual understanding. The research instrument used is coding, and the data analysis method involves descriptive quantitative analysis with a focus on effect size. The results indicate that the implementation of the PBL model has a positive impact on various student abilities, regardless of educational level and type of skill. Thus, the PBL model has proven to be effective in enhancing students' conceptual mastery and HOTS across different educational levels.